IRE1α is critical for Kaempferol‐induced neuroblastoma differentiation. (19th February 2019) - Abdullah, Ahmad; Talwar, Priti; d'Hellencourt, Christian Lefebvre; Ravanan, Palaniyandi
Abstract : Neuroblastoma is an embryonic malignancy that arises out of the neural crest cells of the sympathetic nervous system. It is the most common childhood tumor known for its spontaneous regression via the process of differentiation. The induction of differentiation using small molecules such as retinoic acid is one of the therapeutic strategies to treat the residual disease. In this study, we have reported the effect of kaempferol (KFL) in inducing differentiation of neuroblastoma cells in vitro . Treatment of neuroblastoma cells with KFL reduced the proliferation and enhanced apoptosis along with the induction of neuritogenesis. Analysis of the expression of neuron‐specific markers such as β‐III tubulin, neuron‐specific enolase, and N‐ myc downregulated gene 1 revealed the process of differentiation accompanying KFL‐induced apoptosis. Further analysis to understand the molecular mechanism of action showed that the effect of KFL is mediated by the activation of the endoribonuclease activity of inositol‐requiring enzyme 1 alpha (IRE1α), an endoplasmic reticulum‐resident transmembrane protein. In silico docking analysis and biochemical assays using recombinant human IRE1α confirm the binding of KFL to the ATP‐binding site of IRE1α, which thereby activates IRE1α ribonuclease activity. Treatment of cells with the small molecule STF083010, which specifically targets and inhibits the endoribonuclease activity of IRE1α, showed reduced expression of neuron‐specific markers and curtailed neuritogenesis. The knockdown of IRE1α using plasmid‐based shRNA lentiviral particles also showed diminished changes in the morphology of the cells upon KFL treatment. Thus, our study suggests that KFL induces differentiation of neuroblastoma cells via the IRE1α ‐XBP1 pathway. Abstract : Inositol‐requiring enzyme 1 alpha (IRE1α) is a kinase possessing endoribonuclease activity; its luminal domain is in the endoplasmic reticulum membrane, while the trans‐activating domain is in the cytosol. Binding of the phytoestrogen kaempferol (K) to the kinase domain of IRE1α induces activation of its endoribonuclease activity, splicing of X‐box‐binding protein 1 (XBP1s, a transcription factor), and neuroblastoma differentiation. Pretreatment with STF083010 (S), an inhibitor for IRE1α's endoribonuclease activity, or IRE1α knockdown using shRNA, resulted in inhibition of neuroblastoma differentiation.